PENGARUH TEMPERATUR PADA ISOLASI MIRISTISIN DARI MINYAK PALA MENGGUNAKAN ROTARY EVAPORATOR - The Effect of Temperature on Myristicin Isolation from Nutmeg Oil Using Rotary Evaporator - Ida Hasmita; Eka Marya Mistar; Fauzi Redha (Balai Riset dan Standardisasi Industri Pontianak, 2019)
One of the determination factors of nutmeg oil quality is myristicin content because it gives a distinctive aroma to nutmeg oil. The purification process of nutmeg oil requires a long distillation time thus refining techniques which more efficient with quality results that meet the standards are needed. This study aimed to determine temperature effect on isolation of myristicin from nutmeg oil using a rotary evaporator. The stages of this research were carried out in two stages, namely concentration and purification stage, each using a temperature variation of 140 0C, 145 0C and 150 0C at 300 mbar pressure for 1 hour. The concentration process at a pressure of 300 mbar with a temperature variation of 150 0C for 1 hour process obtained 22.26% myristicin. The next stage of purification of nutmeg oil carried out at a pressure of 300 mbar with a temperature of 150 0C for 1 hour was able to isolate myristicin up to 53.41%. The results of gas chromatography-mass spectrophotometry (GCMS) on nutmeg oil at a pressure of 300 mbar with a temperature of 150 0C for 1 hour process with 53.41% myristicin content had met Indonesian National Standard (SNI) 06-2388-2006 with a minimum value of 10%.Keywords: myristicin, nutmeg oil, rotary evaporatorABSTRAKSalah satu faktor yang mempengaruhi kualitas minyak pala adalah kandungan miristisin, karena memberikan aroma khas pada minyak pala. Proses pemurnian minyak pala membutuhkan waktu penyulingan yang cukup lama sehingga diperlukan teknik pemurnian yang lebih efisien dengan kualitas hasil yang memenuhi standar. Penelitian ini bertujuan untuk mengetahui pengaruh temperatur pada isolasi miristisin dari minyak pala menggunakan rotary evaporator terhadap kadar miristisin. Penelitian dilakukan dalam dua tahap yaitu tahap pemekatan dan tahap pemurnian, masing-masing menggunakan variasi suhu 140 0C, 145 0C dan 150 0C pada tekanan 300 mbar selama 1 jam. Proses pemekatan pada tekanan 300 mbar dengan variasi suhu 150 0C selama 1 jam diperoleh miristisin sebesar 22,26%. Tahapan berikutnya yaitu pemurnian minyak pala yang dilakukan pada tekanan 300 mbar dengan temperatur 150 0C selama 1 jam mampu mengisolasi miristisin hingga 53,41%. Hasil uji gas chromatography-mass spectrophotometry (GCMS) minyak pala pada tekanan 300 mbar dengan temperatur 150 0C selama 1 jam proses dengan kadar miristisin 53,41% telah memenuhi Standar Nasional Indonesia (SNI) 06-2388-2006 dengan nilai minimum 10%. Kata kunci: minyak pala, miristisin, rotary evaporator